BEBERAPA FAKTOR YANG MEMENGARUHI SERVICE PER CONCEPTION PADA SAPI BALI DI KABUPATEN PRINGSEWU - Dwi Haryanto; Madi Hartono; Sri Suharyati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Research on service per conception in Bali Cattles in Pringsewu Regency was held on December 2014 until January 2015 with 5 inseminators, 100 farmers and 131 Bali Cattles that had been inseminated. The purpose of this reserch are to know: 1) value service per conception of Bali Cattles in Pringsewu Regency, 2) the factors and magnitude factors which disturb service per conception of Bali Cattles in Pringsewu Regency. Data was analysis by multifactors regression with SPSS (Statistics Packet for Social Science) program. The result showed that service per conception of Bali Cattles at Pringsewu Regency is 1,79 ± 1,03. Factors that affect the service per conception are distance to acceptors that positively associated with factor value 0,034; correctly inseminator that negatively associated with factor value 1,460; the system of provision of water that positively associated with factor value 1,293; and large cage that negatively associated with factor value 0,008. (Keywords: Service per conception , Bali Cattles, Factor)